Functional Peroxisomes Are Essential for Efficient Cholesterol Sensing and Synthesis - Charles, Khanichi N.; Shackelford, Janis E.; Faust, Phyllis L.; Fliesler, Steven J.; Stangl, Herbert; Kovacs, Werner J. (Frontiers in Cell and Developmental Biology, 2020)
Cholesterol biosynthesis is a multi-step process involving several subcellular compartments, including peroxisomes. Cells adjust their sterol content by both transcriptional and post-transcriptional feedback regulation, for which sterol regulatory element-binding proteins (SREBPs) are essential; such homeostasis is dysregulated in peroxisome-deficient Pex2 knockout mice. Here, we compared the regulation of cholesterol biosynthesis in Chinese hamster ovary (CHO-K1) cells and in three isogenic peroxisome-deficient CHO cell lines harboring Pex2 gene mutations. Peroxisome deficiency activated expression of cholesterogenic genes, however, cholesterol levels were unchanged. 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) protein levels were increased in mutant cells, whereas HMGCR activity was significantly decreased, resulting in reduced cholesterol synthesis. U18666A, an inhibitor of lysosomal cholesterol export, induced cholesterol biosynthetic enzymes; yet, cholesterol synthesis was still reduced. Interestingly, peroxisome deficiency promoted ER-to-Golgi SREBP cleavage-activating protein (SCAP) trafficking even when cells were cholesterol-loaded. Restoration of functional peroxisomes normalized regulation of cholesterol synthesis and SCAP trafficking. These results highlight the importance of functional peroxisomes for maintaining cholesterol homeostasis and efficient cholesterol synthesis.